1992
DOI: 10.2176/nmc.32.671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Therapeutically Induced Hypertension in Patients with Delayed Cerebral Vasospasm by Xenon-enhanced Computed Tomography

Abstract: Serial cerebral blood flow (CBF) measurements were made with stable xenon-enhanced computed tomography in 20 patients with angiographically confirmed ruptured intracranial aneurysms, before and during induced hypertension with continuous infusion of dopamine. All patients showed angiographic vasospasm during their course. Twelve patients without symptomatic vasospasm (Group 1) had the lowest hemispheric CBF on the craniotomy side of 31.6 +/- 6.8 ml/100 gm/min on days 4-9 (control value, 40.1 +/- 2.0 ml/100 gm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
0
20
1
Order By: Relevance
“…18 -20 CBF in the range of 10 to 20 mL · 100 g Ϫ1 · min Ϫ1 has been consistent with the onset of neurological deficits that have been reversible using aggressive revascularization techniques, or with infarction if there is no revascularization, depending on the duration of the ishemia. 19,20,[33][34][35][36][37] Flow values below 10 mL · 100 g Ϫ1 · min…”
mentioning
confidence: 99%
“…18 -20 CBF in the range of 10 to 20 mL · 100 g Ϫ1 · min Ϫ1 has been consistent with the onset of neurological deficits that have been reversible using aggressive revascularization techniques, or with infarction if there is no revascularization, depending on the duration of the ishemia. 19,20,[33][34][35][36][37] Flow values below 10 mL · 100 g Ϫ1 · min…”
mentioning
confidence: 99%
“…Among these, a total of 10 papers were selected, with no randomized trials of induced hypertension identified [17][18][19][20][21][22][23][24][25][26].…”
Section: Blood Pressure Managementmentioning
confidence: 99%
“…In a case series of four patients (3 postoperative) with SAH who had clinical symptoms, dopamine in a dose ranging from 9 to 46 mcg/ kg/min was accompanied by an increase in blood pressure in a range from 160 to 200 mm Hg and associated with symptom improvement [18]. In a cohort study of 20 patients with SAH evaluated with serial CBF measurements, eight patients developed symptomatic vasospasm [19]. CBF increase in response to blood pressure augmentation (mean arterial pressure increase by 20 mm Hg) with dopamine depended on the underlying degree of vasospasm (or underlying reduction in CBF).…”
Section: Blood Pressure Managementmentioning
confidence: 99%
“…Definite conclusions from this design are impossible. In another study, blood pressure elevation to an unspecified target with dopamine did not lead to a difference in cerebral blood flow monitored by serially performed Xenon CT investigations in 20 patients with and without symptomatic vasospasm [9]. Further work compared data from the literature against a management protocol including routine blood pressure elevation, albumin infusion and phlebotomization, mannitol, and dexamethasone used in 43 patients after SAH [3].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Eleven original studies dealing with prophylactic hypervolemic therapy after aneurysmal SAH were identified: four randomized controlled trials (RCTs), two prospective interventional trials, and five observational series using historic controls (Table 1) [2][3][4][7][8][9][10][11][12][13][14]. Together, the RCTs included 244 patients; data from another 531 patients were investigated in the remaining studies.…”
Section: Summary Of the Literaturementioning
confidence: 99%